answersLogoWhite

0


Best Answer

As whole number integers?

4(1) + 1

= 5

------

4(2) + 1

= 9

-----

4(3) + 1

= 13

-------

User Avatar

Wiki User

13y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: What are the first 3 terms for 4n plus 1?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

Solve 4n plus 1 equals 12 plus 5n?

4n + 1 = 12 + 5n First, let's get all n terms on one side and all non-n terms on the other side. Start off by subtracting 4n from each side. 1 = 12 + n Now subtract 12 from each side. -11 = n


What are the first 5 terms of a sequence 4n plus 5?

Starting from 1, your get: [4n + 5] = 9, 13, 17, 21, 25 Basically you find the first one and add 4 each time.


What are the first four terms of the sequence an 4n -1?

5


What is 4n plus 2 times 5n minus one?

20n2+6n-2 (4n + 2)(5n -1) This problem can be solved by FOILing. First, multiply the first terms to get 20n2 Next, multiply the outside terms to get -4n. Multiplication of the inside terms results in 10n. Combining -4n and 10n (they are like terms) is 6n. Then, multiply the last terms, to get -2. Combining these answers into one equation gives the answer of 20n2+6n-2.


What are the first 3 terms for 4n -1?

3 7 11


What is -8n plus 6 plus 4n-7?

It is an expression that can be simplified to -4n-1


What is 4n plus 13 equals 1?

4n+13=1 -13 -134n=-12/4 /4n=-3


What is 4n plus 1 times 2n plus 6?

(4n + 1)*(2n + 6) = 8n2 + 26n + 6


What does n plus 4n-3 equals?

1


What is the answer for 7n plus 6n-5 equals 4n plus 4?

n = 1 7n + 6n - 5 = 4n + 4 13n - 5 = 4n + 4 13n - 4n - 5 = 4n - 4n + 4 9n - 5 = 4 9n -5 + 5 = 4 + 5 9n = 9 n = 1


Solve n for 12 plus 4n equals 2n?

12+4n = 2n12+4n-4n = 2n-4n12 = -2n-1/2(12 = -2n)-6 = n


What is the first 3 terms for the nth term 4n-2?

The first three terms of the nth term 4n-2 would be obtained by plugging in n=1, n=2, and n=3 into the expression. Therefore, the first term would be 4(1) - 2 = 2, the second term would be 4(2) - 2 = 6, and the third term would be 4(3) - 2 = 10. So, the first three terms are 2, 6, and 10 for the given nth term 4n-2.